If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(x + 1) = (-3x + -7)(x + 1) Reorder the terms: (3 + 2x)(x + 1) = (-3x + -7)(x + 1) Reorder the terms: (3 + 2x)(1 + x) = (-3x + -7)(x + 1) Multiply (3 + 2x) * (1 + x) (3(1 + x) + 2x * (1 + x)) = (-3x + -7)(x + 1) ((1 * 3 + x * 3) + 2x * (1 + x)) = (-3x + -7)(x + 1) ((3 + 3x) + 2x * (1 + x)) = (-3x + -7)(x + 1) (3 + 3x + (1 * 2x + x * 2x)) = (-3x + -7)(x + 1) (3 + 3x + (2x + 2x2)) = (-3x + -7)(x + 1) Combine like terms: 3x + 2x = 5x (3 + 5x + 2x2) = (-3x + -7)(x + 1) Reorder the terms: 3 + 5x + 2x2 = (-7 + -3x)(x + 1) Reorder the terms: 3 + 5x + 2x2 = (-7 + -3x)(1 + x) Multiply (-7 + -3x) * (1 + x) 3 + 5x + 2x2 = (-7(1 + x) + -3x * (1 + x)) 3 + 5x + 2x2 = ((1 * -7 + x * -7) + -3x * (1 + x)) 3 + 5x + 2x2 = ((-7 + -7x) + -3x * (1 + x)) 3 + 5x + 2x2 = (-7 + -7x + (1 * -3x + x * -3x)) 3 + 5x + 2x2 = (-7 + -7x + (-3x + -3x2)) Combine like terms: -7x + -3x = -10x 3 + 5x + 2x2 = (-7 + -10x + -3x2) Solving 3 + 5x + 2x2 = -7 + -10x + -3x2 Solving for variable 'x'. Reorder the terms: 3 + 7 + 5x + 10x + 2x2 + 3x2 = -7 + -10x + -3x2 + 7 + 10x + 3x2 Combine like terms: 3 + 7 = 10 10 + 5x + 10x + 2x2 + 3x2 = -7 + -10x + -3x2 + 7 + 10x + 3x2 Combine like terms: 5x + 10x = 15x 10 + 15x + 2x2 + 3x2 = -7 + -10x + -3x2 + 7 + 10x + 3x2 Combine like terms: 2x2 + 3x2 = 5x2 10 + 15x + 5x2 = -7 + -10x + -3x2 + 7 + 10x + 3x2 Reorder the terms: 10 + 15x + 5x2 = -7 + 7 + -10x + 10x + -3x2 + 3x2 Combine like terms: -7 + 7 = 0 10 + 15x + 5x2 = 0 + -10x + 10x + -3x2 + 3x2 10 + 15x + 5x2 = -10x + 10x + -3x2 + 3x2 Combine like terms: -10x + 10x = 0 10 + 15x + 5x2 = 0 + -3x2 + 3x2 10 + 15x + 5x2 = -3x2 + 3x2 Combine like terms: -3x2 + 3x2 = 0 10 + 15x + 5x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(2 + 3x + x2) = 0 Factor a trinomial. 5((2 + x)(1 + x)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-2, -1}
| 4x+3=2(x-5) | | 136/180 | | (5-u)(5u+3)=0 | | Solve(5-u)(5u+3)=0 | | -21x^7-7x^6= | | 8.3+0.6x=11.3 | | X*8+5x=32-2x | | .8=450/x | | 11.3+0.6x=8.3 | | 11.3+8.3x=11.3 | | 3m+27=12 | | -29+(-78)= | | 5+2(3x-6)=15 | | 0.1x^3-1.4x^2+3.5x+5=0 | | 7x^2-42x-189=0 | | 0.78+1.011= | | tanx=1/500 | | [[(1[[[4[[x]^[2]]]/[3[[x]^[6]]]]]1)]^[ eg;[2]]] | | .65x=65 | | X-1+43=180 | | X-1+x+43=180 | | x+2+2x=140 | | 11x+7x=360 | | 3x-45+60=180 | | 5(0)+8(5)+7= | | 3x=4.2-y | | 78.5=3.14r | | 4x-4+3x-2+2x+6=180 | | x^2+4x-765=0 | | 7y+30=4y+60 | | 0.2x^2-1.1x+9.165=0 | | X^4-19x^2+88=0 |